Belief in Unconscious Repressed Memory Persists. (March 2021) - Otgaar, Henry; Howe, Mark L.; Dodier, Olivier; Lilienfeld, Scott O.; Loftus, Elizabeth F.; Lynn, Steven Jay; Merckelbach, Harald; Patihis, Lawrence
On the basis of converging research, we concluded that the controversial topic of unconscious blockage of psychological trauma (i.e., repressed memory) remains very much alive in clinical, legal, and academic contexts. In his commentary, Brewin (this issue, p. 443) conducted a cocitation analysis and concluded that scholars do not adhere to the concept of unconscious repression. Furthermore, he argued that previous survey research did not specifically assess unconscious repression. Here, we present critical evidence that runs counter to his claims. First, we inspected his cocitation analysis and found that some scholars support notions that are closely related to unconscious repression. Furthermore, we conducted another analysis on the basis of articles' similarity. Again, we found examples of scholars specifically endorsing unconscious repressed memories. Second, as opposed to what Brewin reports, recent survey research now exists that bears directly on people's beliefs regarding unconscious repression. This work reveals that large percentages of people (e.g., students and eye-movement desensitization and reprocessing [EMDR] clinicians) endorse the concept of unconscious repressed memories. The belief in unconscious repressed memory can continue to contribute to harmful consequences in clinical, legal, and academic domains (e.g., false accusations of abuse).